Scrutinizing Social Identity Theory in Corporate Social Responsibility: An Experimental Investigation - Paruzel, Agnieszka; Danel, Martin; Maier, Günter W. (Frontiers in Psychology, 2020)
Corporate social responsibility (CSR) is widely established by companies that aim to contribute to society and minimize their negative impact on the environment. In CSR research, employees’ reactions to CSR have extensively been researched. Social identity theory is often used as a theoretical background to explain the relationship between CSR and employee-related outcomes, but until now, a sound empirical examination is lacking, and causality remains unclear. CSR can unfold its effect mainly because of three theoretically important aspects of CSR initiatives, which increase identification, i.e., distinctiveness, prestige, and salience of the out-group. This study examines how far identification can explain the effect of CSR on employees. In an experimental vignette study (N = 136 employees), CSR was manipulated in three degrees (positive, neutral, and negative) to examine its effects on job satisfaction, organizational commitment, and organizational citizenship behavior (OCB). In the vignettes, information on distinctiveness, prestige, and salience of the out-group were presented. Regression analyses showed that CSR significantly predicted commitment and job satisfaction, but not OCB. We found mediation effects of CSR on commitment, job satisfaction, and OCB through identification, but the effect of CSR on identification explained only little variance which indicates additional underlying mechanisms. The applicability of social identity theory for explaining CSR is discussed. Moreover, we discuss further explaining mechanisms.